EPISTEMOLOGI SUFI (Telaah literatur atas definisi Pengobatan cara sufi) - Naan Naan (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2018)
AbstractThe essence of the teachings of the Sufis is with God. The goal is taqarrub ilallah, to get closer to Allah. This close relationship is maintained and arranged in such a way through ritualistic Sufi teachings. The research method used is qualitative. The researcher analyzed the data on the Sufism texts. The results of data processing state that in Sufism, all activities of human life are worship. Worship is not enough with prayer and fasting, but it is perfected with morals. Worship which is accompanied by morals directs salik to perfection, where the physical and mental dimensions are in unity. This unity of identity is what is healthy in Sufism. Healthy in Sufism means physical, mental and spiritual health.